Influence of leadership and organizational culture on employee performance at the Jeneponto regency investment and one-stop integrated service office - Maryadi Maryadi; Muhammad Idris; Sylvia Sjarlis; Yusrab Ardianto Sabban (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to analyze: (1) the influence of leadership and organizational culture partially on employee performance, (2) the influence of leadership and organizational culture simultaneously on employee performance, 3) the influence of leadership directly and indirectly through the reward system on employee performance, (4) direct and indirect influence of organizational culture through the reward system on employee performance at the Jeneponto Regency One Stop Integrated Service and Investment Service. This study uses a quantitative approach, using path analysis. Using a saturated sample, ie all populations are sampled, the results show that: 1) There is a positive and significant influence of leadership and organizational culture partially on employee performance, (2) There is a positive and significant influence of leadership and organizational culture simultaneously on employee performance, (3) Leadership through Reward System either directly and significantly related to employee performance, (4) cultural organizations through Reward System has influence directly and significantly on Employee performance at the Department of Investment and Integrated Services One Stop Jeneponto.